Functional proteomics identify mannitol metabolism in serum resistance and therapeutic implications in Vibrio alginolyticus - Kou, Tian-shun; Wu, Jia-han; Chen, Xuan-wei; Peng, Bo (Frontiers in Immunology, 2022)
Serum resistance is recognized as one of the most important pathogenic traits of bacterial pathogens, and no control measure is available. Based on our previous discovery that pathogenic Escherichia coli represses glycine, serine and threonine metabolism to confer serum resistance, and reactivation of this pathway by exogenous glycine could restore serum sensitivity, we further investigate the mechanism underlying the action of glycine in Vibrio alginolyticus. Thus, V. alginolyticus is treated with glycine and the proteomic change is profiled with TMT-based quantitative proteomics. Compared to the control group, glycine treatment influences the expression of a total of 291 proteins. Among them, trap-type mannitol/chloroaromatic compound transport system, periplasmic component, encoded by N646_0992, is the most significantly increased protein. In combined with the pathway enrichment analysis showing the altered fructose and mannitol metabolism, mannitol is emerged as a possible metabolite in enhancing serum killing activity. To demonstrate this, exogenous mannitol is added to a final concentration of 5 mM that reduce bacterial viability. This synergistic effect is further confirmed in a V.alginolyticus-Danio rerio infection model. Furthermore, the mechanism underlying mannitol-enabled serum killing is dependent on glycolysis and pyruvate cycle that increases the deposition of complements components C3b and C5b-9 on bacterial surface, whereas inhibiting glycolysis or pyruvate cycle significantly weakened the synergistic effects and complement deposition. These data together suggest that mannitol is a potent metabolite in reversing serum resistance of V. alginolyticus and promising to be used in aquaculture.